2011
DOI: 10.1016/j.ejvs.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Rete Mirabile and Pseudoxanthoma Elasticum: An Accidental Association?

Abstract: We report the case of a young female patient with a transient amaurosis due to a carotid rete mirabile (CRM), a rare congenital carotid malformation, and pseudoxanthoma elasticum (PXE), an inherited autosomal recessive systemic metabolic disorder characterised by fragmentation and mineralisation of elastic fibres in connective tissues (skin, eyes) and the vascular system. CRM is a rare form of intracranial carotid malformation whose association with PXE (6 cases at present) would appear not to be accidental. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 4 publications
(5 reference statements)
0
20
0
3
Order By: Relevance
“…Involvement of the vascular wall (particularly in distal vessels) may lower the success of surgical procedures and should prompt the pre-operative assessment of all candidate vessels [33, 34]. Aneurysms [35, 36], stroke [31, 36], transient ischemic attack [36, 37], stenosis of medium-sized arteries such as the radial and carotid arteries [38, 39], and stenosis of the aorta [39] have also been reported. PXE has been described as a unique monogenic model of peripheral artery disease in which arterial wall remodeling is associated with an abnormally low ankle-brachial index (i.e.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Involvement of the vascular wall (particularly in distal vessels) may lower the success of surgical procedures and should prompt the pre-operative assessment of all candidate vessels [33, 34]. Aneurysms [35, 36], stroke [31, 36], transient ischemic attack [36, 37], stenosis of medium-sized arteries such as the radial and carotid arteries [38, 39], and stenosis of the aorta [39] have also been reported. PXE has been described as a unique monogenic model of peripheral artery disease in which arterial wall remodeling is associated with an abnormally low ankle-brachial index (i.e.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…A Belgian PXE cohort ( n = 100) based on self-reported data concluded that it was an unrelated association (van den Berg et al, 2000) while the association between intracranial malformations, including aneurysms, and PXE may not be fortuitous (Vasseur et al, 2011). …”
Section: Clinical Expression Of the Vascular Pxe Phenotypementioning
confidence: 99%
“…Atherosclerotic plaques could co-exist with PXE lesions, but results from our cohort (unpublished data) showed that carotid plaques were absent in 55/93 (59.1%), unilateral in 17/93 (18.3%), and bilateral in 21/93 (22.6%) compared to age and gender-matched controls ( p = 0.987) suggesting that it is not a primary mechanism for stroke in PXE. Transient cerebral ischemic attack could result from intermittent hemodynamic cerebral insufficiency due to intracranial arterial malformation (Vasseur et al, 2011). …”
Section: Clinical Expression Of the Vascular Pxe Phenotypementioning
confidence: 99%
“…The remaining patients were detected incidentally on imaging, except for a single case of carotid–cavernous fistula. Additionally, six cases of carotid RM were associated with pseudoxanthoma elasticum 6. In the present case, the patient presented with features of cerebral venous ischemia.…”
Section: Discussionmentioning
confidence: 56%
“…However, this predisposed the patient to develop cerebral venous ischemia. Our patient had a better prognosis because RM does not necessarily decrease cerebral perfusion although it may decrease perfusion pressure 6. Thus the presence of RM in a patient with VGAM may not cause significant arterial ischemia and should not in itself be considered a contraindication to therapy.…”
Section: Discussionmentioning
confidence: 73%